On Issues and Challenges of Rural Telecommunications Access in Nigeria - Adediran , Y. A.; J.K, J. F. Opadiji; Faruk , N.; Bello , O.W. (African Journal of Education,Science and Technology (AJEST), 2016)
Rural telecommunication access has to do with provision of telecommunication infrastructure in rural communities for the purpose of connectivity within communities and with the rest of the world. There has been growing interest in how to provide universal telecommunication access in developing countries. The trend in digital divide between the rural and urban areas for developing countries reveals a growing gap. Efforts are being made by developed nations to close the gap; hence, there is the need for reversal of this trend by developing nations in their pursuit of sustainable development. The rural communities in Africa, particularly in Nigeria, are strongly faced with many challenges which include extreme poverty, lack of social services and infrastructures, low level of education and health status, as well as unequal access to income opportunities. Despite the fact that telecommunications services in Nigeria could be traced back to 1851, the aforementioned factors, coupled with the difficult physical terrain in some cases, have made them lack behind the urban areas with regard to provision of telecommunications access. In this paper, issues and challenges of providing telecommunications access in the rural areas are provided. The work looks in-depth into the socio-cultural, literacy, security, infrastructure, regulatory and financial sustainability issues. Furthermore, the paper proffers some technological options/solutions to meeting the telecommunications needs of the rural communities in Nigeria within a very short, but reasonable, time.